Psychosocial Impact of Renal Transplantation HIV Positive Patients Living with ESRD - Agarwal, D. K.; Agarwal, Aditya; Nag , Nalin; Gajway, Swapnil Y.; Garanayak, Satyabrat (Research Highlights in Disease and Health Research Vol. 8, 2023)
We studied the impact of renal transplantation on the psychosocial status through a questionnaire which assessed multiple parameters with fixed multiple choice responses. An attempt was made to compare the pre and post-transplant psychosocial status of the patients wherever possible. Donor–recipient relationships might be collaborative interactions in which an individual donates an organ to the other. Transplantation within a family requires the donor and recipient to psychological support each other throughout the transplantation process. Most patients [Nine out of ten (90%)] reported better quality of life, an increase in professional productivity and perceived an improvement in behavior of the spouse and colleagues towards them. Out of the nine patients who were sexually active, seven (77%) experienced an improvement in their sexual relationship. Six patients (60%) responded that they continue to live in constant fear of an HIV relapse even after the surgery, whereas seven patients (70%) recalled that they experienced significant anxiety and feared an unsuccessful transplant and the relapse of HIV before the surgery. They all agreed that high costs and a lack of knowledge about kidney transplantation as a potential treatment option were the main barriers to renal transplantation in HIV-positive patients. Renal transplantation significantly improved the psychosocial status of HIV-positive renal transplant recipients in a number of areas, including quality of life, sex life, and employment opportunities, among others. Even though it made some people nervous and afraid. A larger study involving more participants would unquestionably be more enlightening.